Association Between Visceral Adiposity Marker with Diabetic Kidney Disease: An Analysis of Data from National Diabetes Registry Malaysia - Kamarudin, Syaharatul Patimah; Samsudin, Ely Zarina; Ismail, Zaliha; Ibrahim, Khalid; Bukhary, Noriklil Bukhary Ismail; Suddin, Leny Suzana (International Journal of Membrane Science and Technology, 2023)
Diabetic kidney disease (DKD) causes significant morbidity and mortality and an economic burden to the country. New visceral adiposity assessment and measurements have gained much attention as a surrogate marker to screen pathogenic visceral fat among patients with chronic kidney disease. This study aims to determine the association between visceral adiposity markers and DKD among T2DM patients. A cross-sectional study to analyze Putrajaya Diabetes Clinical Audit 2018 data from the National Diabetes Registry Malaysia was conducted. A universal sampling method was performed to include all T2DM patients in the dataset. Logistic regression analyses were utilized for three visceral adiposity markers, which were the hypertriglyceridemic waist (HW) phenotype, visceral adiposity index (VAI) and lipid accumulation product index (LAPI). A total of 1,297 T2DM patients were included in the analyses. The majority of them were of Malay ethnicity, male and aged between 40-64 years. The overall prevalence of DKD was 24.1%. VAI was significantly associated with DKD among males but not in females. Compared to males in the first VAI quartile group, both second and fourth quartile groups had increased odds of DKD [adjusted odds ratio (AOR) of 1.91 (95% confidence interval [CI]: 1.09, 3.34) and AOR 2.29 (95% CI: 1.03, 5.09) respectively)]. There was no significant association between HW phenotype and LAPI with DKD. VAI could predict DKD only in male T2DM patients. Thus, it might be a useful clinical indicator of DKD in male T2DM patients in primary care.